1997
DOI: 10.1016/s0022-5347(01)65307-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Production by the Spermatozoa of Patients With Idiopathic Infertility: Relationship to Seminal Plasma Antioxidants

Abstract: Decreased seminal plasma antioxidant activity and increased reactive oxygen species production can be responsible for idiopathic male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 20 publications
8
95
1
4
Order By: Relevance
“…In vitro studies have also shown that ROS cause sperm immotility within 5-30 min after addition of lipid peroxide, confirming that motility is very susceptible parameter to lipid peroxidation [16,24]. In comparative studies between infertile and fertile men, mean semen ROS levels were significantly higher in infertile men than those in controls [1,6,32]. Also, total antioxidant capacity (TAC) and seminal plasma antioxidants (superoxide dismutase, catalase, glutathione peroxidase, and total sulfhydryl group) were significantly lower than in controls [6,32,38].…”
Section: Effect Of Vitamin E and Selenium Of Semenmentioning
confidence: 87%
See 1 more Smart Citation
“…In vitro studies have also shown that ROS cause sperm immotility within 5-30 min after addition of lipid peroxide, confirming that motility is very susceptible parameter to lipid peroxidation [16,24]. In comparative studies between infertile and fertile men, mean semen ROS levels were significantly higher in infertile men than those in controls [1,6,32]. Also, total antioxidant capacity (TAC) and seminal plasma antioxidants (superoxide dismutase, catalase, glutathione peroxidase, and total sulfhydryl group) were significantly lower than in controls [6,32,38].…”
Section: Effect Of Vitamin E and Selenium Of Semenmentioning
confidence: 87%
“…In comparative studies between infertile and fertile men, mean semen ROS levels were significantly higher in infertile men than those in controls [1,6,32]. Also, total antioxidant capacity (TAC) and seminal plasma antioxidants (superoxide dismutase, catalase, glutathione peroxidase, and total sulfhydryl group) were significantly lower than in controls [6,32,38]. Iwasaki and Gagnon [23] detected ROS in 40% of semen samples from infertile patients, whereas no ROS was detected in control and azoospermic subjects.…”
Section: Effect Of Vitamin E and Selenium Of Semenmentioning
confidence: 99%
“…[62,63] Oxidative stress has been established as one of the major factors leading to infertility in men. [64] Testicular production of free radicals and activation of the antioxidant defence system following exposure to toxic chemicals has been reported. [65] A role for ROS in infertility due to defective sperm function is also reported.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…In contrast, there were no significant differences between specific and total activity of SOD, GPX and CAT in seminal plasma of two groups. Different studies have investigated antioxidant enzymes of seminal plasma in asthenozoospermic samples or other altered semen parameters but their results remain controversial (11)(12)(13)(14)(15). Results based on this study showed a negative correlation between specific activity of CAT and SOD with MDA content of spermatozoa from normozoospermic samples.…”
Section: Commentsmentioning
confidence: 99%
“…The question of whether seminal plasma SOD, GPX and CAT can act coordinately to protect human spermatozoa from lipid peroxidation has not to date been systematically addressed, although the presence of SOD, GPX and CAT activity in seminal plasma from fertile and infertile men has been reported (11)(12)(13)(14)(15). Since lipid peroxidation leads to loss of motility in human spermatozoa, the possibility exists that asthenozoospermic sperm suffers from the lack of protection against lipid peroxidation due to lack of adequate or non-coordination between SOD, GPX and CAT activity in seminal plasma.…”
Section: Introductionmentioning
confidence: 99%